Epr1, a UPR-upregulated soluble autophagy receptor for reticulophagy. Issue 11 (1st November 2020) - Zhao, Dan; Du, Li-Lin
ABSTRACT: The endoplasmic reticulum (ER) is a major site of protein folding. Perturbations in the folding capacity of the ER result in ER stress. ER stress triggers autophagic degradation of the ER (reticulophagy). Molecular mechanisms underlying ER stress-induced reticulophagy remain largely unknown. Our recent study identified a soluble protein, Epr1, as an autophagy receptor for ER stress-induced reticulophagy in the fission yeast Schizosaccharomyces pombe . Epr1 can interact simultaneously with Atg8 and a VAP family integral ER membrane protein, and thereby act as a bridging molecule between them. VAP family proteins contribute to reticulophagy by not only connecting Atg8 to the ER membrane through Epr1, but also by supporting the ER-plasma membrane contact. The expression of Epr1 is upregulated during ER stress in a manner dependent on the unfolded protein response (UPR) regulator Ire1. Ire1 promotes reticulophagy by upregulating Epr1.